Detection of Culex flavivirus (Flaviviridae) from a natural Culex (Culex) chidesteri Dyar, 1921 population, Caatinga Biome, Semiarid Scrubland, Brazil - Araújo, Josélio M. G.; Freire, Renato C. M.; Costa, Diego M. P.; Sousa, Denise M. C.; Sousa, Daíse M. C.; Monteiro, Joelma D.; Branco, Mário S. D.; Farias, Kleber J. S.; Fernandes, José V.; La Corte, Roseli; Barbosa, Taciano M.; Gama, Renata (Entomological Communications, 2021)
The first detection of Culex flavivirus (CxFV) in mosquitoes was described in 2007 in Japan and subsequently in different areas of the Americas, Africa, and Asia. In this study, we report the identification of CxFV in Culex (Culex) chidesteri Dyar, 1921 mosquitoes collected in the Açu National Forest - FLONA/ AÇU-RN, a preserved area of Biome Caatinga, State of Rio Grande do Norte, Brazil. We performed nucleotide-sequencing analysis in order to compare with other previously identified CxFV collected from around the world. A total of 129 samples (pools of ≤30 female mosquitoes) were processed for generic reverse transcriptase PCR assay. CxFV infection was identified in only two pools from Culex chidesteri. Our phylogenetic analysis revealed that the AssuCxFV identified in this study belongs to the Africa/Caribbean/South America Subtype. Our study represents the first report of the CxFV from a natural Culex chidesteri population.